Special types of the human manifestation in understanding poetry - Kregždė, S. (Psichologija, 1962)
Research of students' individual differences has great theoretical and practical significance. That's why we chose our objective: to experimentally find out Pavlov's special types of human manifestations during comprehension of poetry. It turned out that according to reading and retelling of emotional, imaginative, and actualization level, as well as according to the rhythm of the peculiarities of perception, all the participants of our experiment can be divided into three groups. The research subjects who rapidly perceived rhythm and did not detect any rhythm error can be assigned to the first group. Representatives of this group try to read poems expressively. They often outwardly show involvement in a poem during reading time. In general, this group's representatives understood the poem immediately. However, their storytelling lacks connections between individual, brightly expressed, and emotional distress imagery. This group's research subjects did not always successfully understand the basic idea of the poem. The reason should be regarded as insufficient Signal II system activity during very active Signal II system activity. This group was 24% (18) of the students in our research. They can be assigned to Pavlov's specified artistic type. The second group consisted of subjects whose sense of rhythm was weaker. They made rhythm errors in reading the poem. Their reading was characterized by monotony and inexpressiveness. They were not interested in verse. They only paid attention to the story. In their storytelling and oral film scripts they tried to convey the main idea of the poem. However, what was conveyed was not a recreation of the author’s imagery, but rather an oral reading form. This group's subjects understanding and comprehension can be explained by the lack of the Signal I system activity. More or less 22% (16) of students in our experiment were characterized this way. These are the thinkers Pavlov described. The third group consists of research subjects who read the poem and did not make major mistakes. They tried to read expressively. They were drawn to verse. Their storytelling and oral film scripts' main idea of the poem was conveyed accurately and thoughtfully. This testifies to the equally activated Signal I and Signal II systems. This group's research subjects' narrations displayed a different of thinking and imagery level; it was probably determined by their age, previous experience, methodological requirements, and the common skills. This group accounts for 54% (40) of students in the experiment. This is the secondary type described by Pavlov.
Keywords: poetry; individual differences; Pavlov's typology